Feasibility Study: Online Learning for Supporting Rural Renewable Energy Projects - Meredita Susanty; Erwin Setiawan; Ariana Yunita; Herminarto Nugroho (Universitas Islam Sultan Agung, 2020)
Indonesian government set the target for new and renewable energy (NRE) is expected to be 23% in 2025 and 31% in 2050, where in 2017, NRE was only 12,5%. Building a new and renewable energy project is the easy part. Keeping the generator working over time, however, is a complex business that requires money, training and innovative thinking. One of essential parameters that can help in achieving a successful sustainable project is community involvement. If the community feels a strong sense of ownership, they'll see their generator as a critical asset to everyone and take good care of it collectively. Training and educating the community about how to take care of the generator after the project construction has completed becomes important. Considering Indonesia’s geographical location, e-learning might be a potential tool to reduce training and education cost in new and renewable project. This study aims to identify whether e-learning is an effective and efficient method to deliver training material and educate local people which will improve renewable energy project’s sustainability in Indonesia.